A time for locally driven development in Papua and West Papua. Issue 6 (18th August 2019) - Indrawan, Mochamad; Sumule, Agus; Wijaya, Arief; Kapisa, Noak; Wanggai, Frans; Ahmad, Mubariq; Mambai, Benja V.; Heatubun, Charlie D.
ABSTRACT: The vast biocultural diversity of Tanah Papua (Land of Papua) are important resources for local economic development, especially where their sustainable use incorporates affirmative action to ensure that indigenous communities capture the resulting benefits. Papuan stakeholders already have their own detailed plans, and there are some success stories to instil confidence in the abilities of the indigenous peoples of Papua to lead their own development. Multi-stakeholder approaches are known to work well, and in this case, locally driven initiatives are also known to be promising. This viewpoint suggests the need for a balance between inclusive participation in multi-stakeholder programmes and the enhancement of locally driven initiatives.